2013
DOI: 10.1111/ejh.12150
|View full text |Cite
|
Sign up to set email alerts
|

Serum hepcidin and growth differentiation factor‐15 (GDF‐15) levels in polycythemia vera and essential thrombocythemia

Abstract: The levels of GDF-15 were higher in CMPD, which are characterized by increased erythropoiesis, and this effect was more pronounced particularly in individuals with JAK2-V617F mutation. Hepcidin levels were not suppressed despite the increased erythroid activity and GDF-15 levels may be protective against the clinical complications of the disease such as thrombosis. This study revealed that, hepcidin levels were not suppressed despite increased erythroid activity and high GDF-15 levels in CMPD. We hypothesized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
15
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 28 publications
5
15
1
Order By: Relevance
“…Our observation of a weak correlation between GDF-15 and hepcidin levels was consistent with published data [26,29], indicating that GDF-15 may not directly influence hepcidin levels [30,31].…”
Section: Discussionsupporting
confidence: 92%
“…Our observation of a weak correlation between GDF-15 and hepcidin levels was consistent with published data [26,29], indicating that GDF-15 may not directly influence hepcidin levels [30,31].…”
Section: Discussionsupporting
confidence: 92%
“…[18] However, it is not clear which factors determine microcytosis in PMF. On MVA, one of the factors associated with microcytosis was low satTF.…”
Section: 0 Discussionmentioning
confidence: 99%
“…Recent translational studies found no significant contribution of GDF15 levels to hepcidin suppression in iron deficiency [46,47], anemia of chronic disease [47] or chronic myeloproliferative diseases [48]. Phlebotomy of wild-type and Gdf15 −/− mice showed similar suppression of hepatic hepcidin mRNA in both groups of mice [49 ■ ].…”
Section: ‘Erythroid Regulators’ Of Hepcidin Expressionmentioning
confidence: 99%